Auditors' Evaluation of Test-of-Control Strength - Spires, Eric E. (The Accounting Review, 1991)
[Evaluating the strength of audit evidence is a primary activity of auditors, but little is known of the factors that affect these evaluations. This article identifies and investigates two factors that affect auditors' evaluations of evidence strength. The first factor deals with underlying constructs of evidence, called strength dimensions in this study. Although the auditing literature suggests that evidence strength is determined by such underlying constructs (see, e.g., AAA ASOBAC 1973; AICPA 1980, 1988), prior research has focused on the surface characteristics of evidence. Hence, "source of evidence" has been studied (see, e.g., Joyce and Biddle 1981; Knechel and Messier 1990; Rebele et al. 1988) rather than the underlying strength dimension of "validity" (see AICPA 1980, AU 326). The present study focuses on the underlying dimensions to determine whether they provide a basis for understanding auditors' evaluations of evidence strength. The second factor concerns accounting firms' policies for auditing procedures. Firms' policies represent different methods of conducting efficient and effective audits (Cushing and Loebbecke 1986), and it is likely that these policies influence field auditors' judgments. Therefore, prior research on how accounting firms' degrees of structure affect auditors' judgments is extended to include the effects of specific policies. Auditors' evaluations of test-of-control strength were used to assess whether underlying dimensions of evidence strength and the specific policies of accounting firms affect auditors' judgments. Tests of controls (TCs) are auditing procedures that determine the effectiveness of an internal control; TC strength is the degree of assurance about a control's effectiveness provided by evidence generated by a TC. In this study, TC strength is defined and evaluated along the dimensions of validity, verifiability, and coverage. Auditors evaluated five TCs along the three strength dimensions to provide dimension-based rankings of TC strength. Other auditors participated in a laboratory experiment that involved control risk assessment. Correlations between the implied ranking of TC strength from the experiment and the dimension-based rankings are high, positive, and statistically significant, which suggests that auditors' judgments of evidence strength reflect the professional standards. Conversely, studies of audit adjustments have shown that evidence strength (measured as the ability to initially detect errors) does not strongly reflect the standards. The discrepant results suggest that characterizations of evidence strength may need to be studied further. To assess the effect of accounting firm policies on judgments, I develop predictions about the effects of policies that require reperformance and those that caution about the relative weakness of inquiry and observation. Because the predictions are largely confirmed by auditors' judgments in the laboratory experiment, accounting firms' policies are deemed to influence audit judgments. If generalizable, this finding suggests that results of research studies may be affected by the policies of accounting firms supplying subjects or data, to the extent that firms' policies differ. Researchers should therefore become familiar with firm-specific policies. For practitioners, this finding indicates that setting firm-wide policies may be effective in influencing field auditors' judgments.]